2010
DOI: 10.1100/tsw.2010.187
|View full text |Cite
|
Sign up to set email alerts
|

High Origin of Radial Arteries: A Report of Two Rare Cases

Abstract: Variations in the arterial supply of the upper limb are relatively common, with reported prevalence rates ranging from 11 to 24.4%. Of these, the most commonly encountered variation in the arm is a high origin of the radial artery. However, after consecutively dissecting and examining 600 Singaporean Chinese cadavers (1,200 upper limbs), we found only two cases of this. In both cases, the brachioradial artery originated from the upper one-third of the brachial artery and continued distally as the radial artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…We registered this variation in 6.38% (27/423) which ranks it the most common variation of the arm and forearm longitudinal arterial trunks in our study as well as in other cadaveric studies [ 1 , 3 , 6 , 9 , 11 , 12 , 15 , 16 , 45 - 50 ] – as well as radiographic or ultrasound studies – [ 25 , 51 - 58 ] – although Zhan et al (2010) reported only two cases out of 1200 limbs examined in Singapore Chinese population [ 48 ]. Based on Lippert and Pabst (1985) review [ 14 ], it is present in 8% (3% with cubital anastomosis) but the prevalence data differ a lot ( Table 7 ).…”
Section: Resultssupporting
confidence: 76%
“…We registered this variation in 6.38% (27/423) which ranks it the most common variation of the arm and forearm longitudinal arterial trunks in our study as well as in other cadaveric studies [ 1 , 3 , 6 , 9 , 11 , 12 , 15 , 16 , 45 - 50 ] – as well as radiographic or ultrasound studies – [ 25 , 51 - 58 ] – although Zhan et al (2010) reported only two cases out of 1200 limbs examined in Singapore Chinese population [ 48 ]. Based on Lippert and Pabst (1985) review [ 14 ], it is present in 8% (3% with cubital anastomosis) but the prevalence data differ a lot ( Table 7 ).…”
Section: Resultssupporting
confidence: 76%
“…The incidence of high-origin RA varied from 5.9% to 12.1% among Caucasians, but it was lower in Korean cadavers, at only 2.3% 17) . However, in Singaporean Chinese cadavers, high-origin RA was found in even fewer patients, with only a 0.33% prevalence 18) . Although the differences in the RA origin among races have no clear explanation, racial differences are of great importance in clinical practice.…”
Section: Discussionmentioning
confidence: 90%